Occurrence of ceramides in the Acidobacterium Solibacter usitatus: implications for bacterial physiology and sphingolipids in soils - Halamka, Toby A.; Garcia, Andy; Evans, Thomas W.; Schubert, Stephanie; Younkin, Adam; Hinrichs, Kai-Uwe; Kopf, Sebastian (Frontiers in Geochemistry, 2024)
Sphingolipids have long been of interest to the scientific community for their roles in eukaryotic cell structuring and disease pathology. Less is known about the occurrence and function of these diverse compounds in the bacterial domain of life, with most studies on bacterial sphingolipids focused on eukaryotic disease research and host-pathogen or host-symbiont interactions. Thus, bacterial contributions to environmental sphingolipid pools are poorly understood and the function of these lipids outside of pathogenicity remains largely unexplored. This report marks the first instance of sphingolipid production in a member of the phylum Acidobacteria, a globally ubiquitous phylum of soil bacteria. The occurrence of core-and intact-ceramides is reported for the Acidobacterium Solibacter usitatus under various environmentally relevant conditions. Shifts in the production of ceramides across temperature, pH, and oxygen gradients in this organism suggest that these compounds play a role in the physiological adaptation to environmental fluctuations. Additionally, the genetic basis of bacterial ceramide biosynthesis in this species is assessed and used to explore the potential for ceramide biosynthesis across the bacterial domain of life. The extent of the biosynthetic potential for Acidobacteria to produce ceramides coupled to the abundance of their genes in soil metagenomes suggests that soil sphingolipids should not be solely attributed to eukaryotic production.